Research on the application of LEO satellite communication and Internet of things - Yang LIU; Feng WEI; Shucheng CUI; Wenjian WANG (物联网学报)
Relying on the demands of Internet of things application,a detailed review on the status quo of LEO (low earth orbit) satellite communication system was given,and the components of communication system were compared and explained separately.Afterwards,the characteristics of the NB-IoT land-based communication network widely applied at present and existing LEO satellite communication system were compared,and a feasible design scheme for IoT-oriented LEO satellite system was provided,and its main parameters and characteristics were briefly described.